The reality of mental health at work among the category of nurses in light of the Covid 19 pandemic: the job burnout syndrome as a model - Mars, Hana (Journal of Human Sciences, 2024)
This study addressed the subject of mental health at work under the Covid 19 pandemic, with the aim of knowing the level of psychological combustion in the category of nurses, highlighting the levels of emotional stress, sedation of feelings, and lack of sense of achievement. This study was conducted at the Hospital Foundation (Hafed Boudjemaa), which was converted into the Covid cell in Constantine state, the study sample included (163) nurses, we adopted the analytical descriptive approach that is in line with the nature of the study, the research tool was the Maslash scale of psychological combustion, the arabic version, where the results of the study achieved the general hypothesis that "nurses suffer from a high level of psychological combustion under the Covid pandemic.